Comparative study of PWM and PDM in Class D Amplifiers - Lebbihi Laid; Amamra Abdel-Latif (University of Shahid Hama Lakhdar - El Oued, 2024)
Pulse width modulation (PWM) and pulse density modulation (PDM) are among the most important modulation techniques in demand today, especially in amplifiers. As amplifiers are divided into several classes, class D is the best one, providing high efficiency and low dissipation. This master’s dissertation is dedicated to a comparative study of PWM and PDM in Class D amplifiers and their effect on their performance through circuit complexity, simplicity, efficiency, and dissipation. PWM outperforms PDM in terms of circuit simplicity, performance, and cost-effectiveness, making it the preferred choice for Class D amplifiers. يعد تعديل عرض النبض (PWM) وتعديل كثافة النبض (PDM) من بين هذه التقنيات من أهم تقنيات التعديل المطلوبة اليوم، خاصة في مكبرات الصوت. مثل تنقسم مكبرات الصوت إلى عدة فئات، الفئة D هي الأفضل، حيث توفر كفاءة عالية وتبديد منخفض. إن رسالة الماجستير هذه مخصصة لدراسة مقارنة بين PWM و PDM في مكبرات الصوت من الفئة D وتأثيرها على أدائها من خلال تعقيد الدوائر، البساطة والكفاءة والتبديد. يتفوق PWM على PDM من حيث بساطة الدائرة، الأداء والفعالية من حيث التكلفة، مما يجعله الخيار المفضل لمكبرات الصوت من الفئة D
Mémoires de Master : spécialisation communications filaires et non filaires
Keywords: PWM; PDM; Class-D amplifier; Circuit; THD; Efficiency; PWM، PDM، مكبر للصوت من الفئة D، الدائرة، THD، الكفاءة